Ultrasonic-assisted synthesis of carbodiimides from N,N′-disubstituted thioureas and ureas - Duangkamol C. (2017)
© 2016, Springer-Verlag Wien. A facile and efficient sonochemical method for the preparation of carbodiimides from their corresponding thioureas or ureas was described. Using Ph 3 P–I 2 combination in the presence of triethylamine, various diaryl, aryl–alkyl, as well as dialkyl substituted substrates could be converted into carbodiimides in good-to-excellent yields within short reaction times under mild conditions with simple experimental setup. Graphical abstract: [Figure not available: see fulltext.]